The Effects of Short-Term Heavy Load Squat vs. Moderate Load Olympic Weightlifting Training on Maximal Strength and Force–Velocity Profile in Young Female Handball Players - Gergely Pálinkás; Csaba Ökrös; Zsófia Tróznai; Katinka Utczás; Leonidas Petridis (Journal of Functional Morphology and Kinesiology)
Objectives: This study examined changes in maximal strength and the force–velocity (FV) profile in young female handball players following an in-season heavy load squat or a moderate load Olympic weightlifting short-term training intervention. Methods: A total of 27 active young female handball players (age: 17.6 ± 0.98 years; height: 168.9 ± 5.1 cm; weight: 64.9 ± 10.6 kg) participated. 5RM back squats and unloaded and loaded countermovement jumps were assessed to establish the FV profile. Participants were divided into the following groups: the control group (CG; n = 8) followed its usual strength training including bodyweight exercises, the heavy load squat group (SQUAT; n = 7) performed heavy load back squats, and the Olympic weightlifting group (OWG; n = 12) used moderate load weightlifting derivates. Results: Absolute and relative 5RM back squat and vertical jump height increased in both intervention groups (5RM from 56.8 ± 5.5 to 62.2 ± 5.3 kg, p < 0.05 and CMJ height from 26.7 ± 4.7 to 28.4 ± 4.9 cm, p < 0.05 for SQUAT; 5RM from 56.6 ± 6.8 to 66.1 ± 6.9 kg, p < 0.05 and CMJ height from 26.9 ± 3.0 to 28.3 ± 3.2 cm, p < 0.05 for OWG), but not in the CG (5RM from 63.8 ± 12.5 to 63.4 ± 12.9 kg, CMJ height from 28.4 ± 2.2 to 27.7 ± 2.9 cm). The FV profile did not change significantly in either group. The theoretical maximal force remained almost unchanged in the SQUAT and OWG (+2% each), while only the OWG could slightly decrease FV imbalance (−14%). Conclusions: Both strength and Olympic weightlifting short-term training could improve strength and explosive performance, but without affecting the FV profile in young, less skilled female handball players. Olympic weightlifting may offer a slight advantage due to its potential to improve power production while optimizing FV imbalance.